1993
DOI: 10.1007/bf03217245
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among mathematics achievement, affective variables and home background

Abstract: One thousand seven hundred and sixty six secondary school students in Hong Kong participated in the present study, in which the relationship among mathematics achievement, affective variables and home background was investigated. It was found that mathematics achievement was most closely related with self-concept, academic self-concept and attitudes towards mathematics. Self-and parental expectations were the most influential factors to these affective variables. It was also found that Hong Kong students spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Given that some recent studies have tapped into domain-specific aspects of homework (e.g., effort and self-regulation; Hong, Peng, & Rowell, 2009;Trautwein, Ludtke, Schnyder, & Niggli, 2006), it would be beneficial to examine homework management in mathematics in the present study in that mathematics is an important achievement domain with typically high demands for homework. It has been shown that students often spend about one-fifth to two-fifths of their homework time on mathematics homework (Kitsantas, Cheema, & Ware, 2011;Pezdek, Berry, & Renno, 2002;Wong, 1992;Wong, Lam, Wong, Leung, & Mok, 2001). Thus, it would be highly important to evaluate psychometric properties of the HMS for mathematics so that educators may use the HMS to better monitor and support students' efforts in managing mathematics homework, and with certain aspects of homework management in particular (e.g., managing time and dealing with negative homework emotions).…”
Section: Introductionmentioning
confidence: 99%
“…Given that some recent studies have tapped into domain-specific aspects of homework (e.g., effort and self-regulation; Hong, Peng, & Rowell, 2009;Trautwein, Ludtke, Schnyder, & Niggli, 2006), it would be beneficial to examine homework management in mathematics in the present study in that mathematics is an important achievement domain with typically high demands for homework. It has been shown that students often spend about one-fifth to two-fifths of their homework time on mathematics homework (Kitsantas, Cheema, & Ware, 2011;Pezdek, Berry, & Renno, 2002;Wong, 1992;Wong, Lam, Wong, Leung, & Mok, 2001). Thus, it would be highly important to evaluate psychometric properties of the HMS for mathematics so that educators may use the HMS to better monitor and support students' efforts in managing mathematics homework, and with certain aspects of homework management in particular (e.g., managing time and dealing with negative homework emotions).…”
Section: Introductionmentioning
confidence: 99%
“…Simon, 1967). Nowadays, non-cognitive predictors of performance (House, 1995) are seen as pertinent in studies of learning: beliefs, attitudes and emotions towards mathematics are an inextricable component of general mathematical performance (Reynolds & Walberg, 1992;Wong, 1992;Jones & Young, 1995;Ma, 1997;Hensel & Stephens, 1997) as well as particular mathematical skills (e.g. abstract mathematical thinking [Iben, 1991]; problem-solving [Kloosterman & Stage, 1992;McLeod, 1993]).…”
Section: Introductionmentioning
confidence: 99%
“…Hattie (2009) emphasised that self-efficacy, self-concept, motivation, engagement, and persistence were highly correlated with performance. Further, attitudes towards mathematics have often shown positive relationships in mathematics performance (Chow 2011;Kumar and Morris 2005;Wong 1993). Students who have shown positive attitudes towards mathematics have performed better in their mathematics performance (Chow 2011).…”
mentioning
confidence: 99%